Pelatihan Networking Fundamental Dan Cyber Security Di SMK Al-Amin Kilang Guna Meningkatkan Kompetensi Guru Dan Siswa - Sadali, Muhamad; Harianto, Harianto; Sudianto, Aris; Wasil, Muhammad; Mahpuz, Mahpuz; Suhartini, Suhartini; Ahmadi, Hamzan; Permana, Baiq Andriska Candra; Gunawan, Indra; Kertawijaya, Lalu; Fathurrahman, Imam (Jurnal Teknologi Informasi untuk Masyarakat, 2023)
Vocational High School (SMK) is a formal education unit that organizes vocational education at the secondary education level as a continuation of SMP/MTs. There are several  programs specifically for SMK students to increase their scientific capacity and competence. Among the programs intended for SMK students are apprenticeship programs or field work practices (PKL), and UKK (Special Competency Test) which are held as graduation requirements. Furthermore, the program invites Guest Teachers from agencies or outside companies. Besides that, SMK students are also asked to create an entrepreneurship program to train students in the field of private entrepreneurship. The Informatics Engineering Study Program often conducts coaching as Guest Teachers for SMK students to improve their knowledge and skills. In addition, the Informatics Engineering Study Program, Faculty of Engineering, routinely organizes skills training every year to prepare for competency exams, where the competency skills that the Informatics Engineering study program has fostered include Expertise Competence in the fields of Computer and Network Engineering, Software Engineering and Multimedia, where the students who participated in this training came from several vocational high schools in East Lombok Regency. Therefore, to improve quality in terms of the quality of knowledge and skills for teachers and students, on this occasion the Informatics Engineering study program would like to hold a Skills competency training, especially in the field of computer and network engineering, to help teachers and students to have the knowledge and skills qualified. Teachers can provide sound knowledge and expertise to students so that students have good abilities and competencies according to the needs of the industrial world. Keywords: Computer Network Engineering, Training, SMK Expertise.